ROAD TRAFFIC SAFETY: A CASE STUDY OF THE PILA POVIAT IN POLAND - Piotr GORZELANCZYK; Aleksander HUK (Scientific Journal of Silesian University of Technology. Series Transport, 2022)
Every year, many road accidents occur on Polish roads, in which many people lose their lives and health. Therefore, an attempt was made to analyze road accidents in the Piła poviat. The source of the analysis were the authors' observations and statistical data. This study was conducted on a sample of 250 inhabitants. Hence, a questionnaire was used. Most people, more than half, about 56%, travel by car because it is a more convenient and faster means of transport. While 35% of respondents stated that they feel relatively safe on the roads. A majority, 65%, of the respondents did not participate in a road accident. Further, 60% of the respondents replied that there were many accidents in the Piła poviat, and only 11% answered that there were not many accidents. According to the respondents, the biggest cause of the accidents is alcohol, inattention of drivers and haste. Despite the information, advertisements, scale of these accidents, and opinions of family and friends, people still drive under the influence of alcohol. Year by year, the number of accidents on the roads of the Piła poviat is low, but still considerably high. There is no best way to stop this from happening. In Piła itself, circular intersections have been introduced to improve safety, such an operation is one of the methods for smoother traffic. Additionally, in residential areas, there are more speed bumps to reduce the speed of vehicles. The conclusions obtained in this article can be successfully implemented, not only in other cities in Poland but also in Europe as well.